Nutrient intake, digestibility and nitrogen retention in indigenous goats fed on Acacia nilotica fruits treated for condensed tannins - Tshabalala, T.; Sikosana, J. L. N.; Chivandi, E. (South African Journal of Animal Science, 2021)
Polyethylene glycol (PEG 4000), Browse PlusTM (BP), wood ash (WA) and boiling water were evaluated as tannin deactivation methods on tannins in Acacia nilotica fruits. Twenty four Matebele goats of mean body mass, 38.7 ± 3.12 kg, were used in a digestibility and nitrogen balance trial. A completely randomized design was used, and the initial weight was used as a covariate in data analysis. The goats were randomly allocated to the treatments and were fed for 28 days on a basal diet of hay and A. nilotica fruits treated with PEG (MW 4000), BP, WA or boiling water. Acacia nilotica fruits had 4.39% catechin equivalents of condensed tannins, thus the amount of PEG, BP and WA used to treat the fruits was 1.5 parts per part of condensed tannin in the fruits. It was hypothesized that treating the fruits would deactivate the tannins in them and increase intake, digestibility and nitrogen retention. Treating the fruits for condensed tannins had no effect on hay and fruit intake. None of the treatments had an effect on the apparent digestibility of dry matter, organic matter, neutral and acid detergent fibre and nitrogen retention in the goats. The goats that were fed on the boiled fruits had a negative N retention of -1.03 g/day. It was concluded that none of the detannification methods improved feed intake, apparent nutrient digestibility and nitrogen retention. It is recommended that each detannification method should be tested on different types of tannins and at different concentrations before totally dismissing the treatments as not useful.